Composite solder sheet and preparation method of AMB ceramic copper-clad plate

By using composite solder sheets containing active metal layers and high-temperature vacuum brazing technology, the problems of high cost and complex process in the existing ceramic copper clad AMB preparation method are solved, and low-cost and high-efficiency AMB ceramic copper clad preparation is achieved, with excellent interface bonding strength and joint reliability.

CN119635073APending Publication Date: 2025-03-18宁波众远新材料科技有限公司 +1

Patent Information

Application Number
CN202510133920.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the existing AMB preparation method for ceramic copper clad AMB, precious metals such as Ag and Au are used, resulting in high raw materials costs and limiting their industrial application scope. At the same time, the multi-layer sputtering process is complicated and it is difficult to achieve large-scale production.

Method used

Using a composite solder sheet containing an active metal layer, a copper-containing layer is deposited on the surface of the active metal foil to form a copper metal layer/active metal layer/copper metal layer structure, and is used for the preparation of AMB ceramic copper clad plate. The method includes high temperature brazing in a vacuum brazing furnace, controlling the heating temperature and insulation time to achieve alloying and wetting metallurgy reaction of the solder.

Benefits of technology

It effectively reduces the preparation cost and improves the preparation efficiency. The processed AMB ceramic copper clad plate has excellent interface bonding strength, low weld void rate and high joint reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119635073A_ABST
    Figure CN119635073A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of circuit substrate manufacturing, and particularly discloses a preparation method of a composite solder sheet and an AMB ceramic copper-clad plate. The composite solder sheet is composed of an active metal foil and a copper-containing layer modified on the surface of the active metal foil, and the preparation method of the copper-clad plate comprises the following steps: after the surface of the active metal foil is pretreated, the copper-containing layer is deposited to prepare the composite solder sheet, and the composite solder sheet is placed between a copper substrate and a ceramic sheet to be pressed and assembled. And performing vacuum brazing on the assembly to complete the preparation of the ceramic copper-clad plate. A composite solder sheet containing active metal is adopted, high-temperature element diffusion during vacuum brazing is utilized at the diffusion temperature to achieve alloying of a composite solder layer, and then heat preservation is conducted at the brazing temperature to achieve uniform melting of solder and wetting metallurgical reaction between the solder and copper and between the solder and a ceramic substrate. By means of the preparation method, low-cost and high-reliability preparation of the AMB ceramic copper-clad plate can be achieved, and the prepared AMB ceramic copper-clad plate also has high peel strength and lower weld porosity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of circuit substrate manufacturing, and in particular relates to a preparation method of a composite solder sheet and an AMB ceramic copper-clad laminate. Background Art

[0002] Ceramic copper clad laminate (CCL) is a circuit substrate structure that is widely used in RF power amplifier devices, laser diodes, IGBT (insulated gate bipolar transistor) and other components, and plays an important role in the field of electronic manufacturing. Ceramic copper clad laminate consists of two parts: a ceramic substrate and a copper metal layer. The ceramic substrate is usually made of silicon nitride, alumina and other materials with excellent insulation, thermal conductivity, high temperature stability and thermal shock resistance. Therefore, it also has the high mechanical strength, low expansion coefficient, moisture and high temperature resistance of ceramic materials and the excellent high conductivity and high thermal conductivity of copper metal. It is very suitable as a power device packaging substrate. The preparation methods of ceramic copper clad laminates mainly include DBC (direct copper cladding method), DPC (direct copper plating method), AMB (active metal brazing method), etc. Among them, DBC and DPC have the advantage of low cost, but the copper clad laminates produced by them have poor circuit accuracy and thin copper layer, which are not suitable for the application requirements of high-power and high-precision semiconductor devices. In comparison, the AMB method can achieve high-strength connection between ceramic and copper metal layers, and is suitable for the preparation of high-precision, thick copper layer ceramic copper-clad laminates. It is currently the most promising method for preparing ceramic copper-clad laminates.

[0003] At present, the prior art has disclosed a lot of research on the preparation method of ceramic copper-clad laminates AMB; for example, Chinese patent application number 202111085679.5 discloses an AMB ceramic-metal brazing method, which proposes the use of Ag-based solder paste to braze copper and ceramic plates; Chinese patent application number 2022107002214 discloses low-voiding ceramic copper-clad laminates and preparation methods thereof, which proposes the use of billets containing precious metals such as Ag and Au and copper substrates to prepare pre-welding layers, and then high-temperature brazing to complete the preparation of ceramic copper-clad laminates. Although the above preparation methods can improve the reliability of the bonding between the ceramic substrate and the copper metal layer, the above inventions all use precious metals such as Ag and Au as solder components, and the cost of raw materials is relatively high, which limits their scope of industrial application. The Chinese patent application number 2019109539833 also discloses a method for preparing a ceramic-based copper-clad laminate, which proposes to sputter active metals, solder and copper substrate onto the ceramic surface in sequence, and then connect the copper plate and the ceramic substrate by vacuum brazing; although the patent does not use precious metals as raw materials, the multi-layer sputtering process brings problems such as high process cost and complex process, making it difficult to achieve mass production. Therefore, it is necessary to invent a highly active composite brazing material to achieve low-cost and high-efficiency preparation of AMB ceramic copper-clad laminates. Summary of the invention

[0004] In view of the prior art, the present invention provides a method for preparing a composite solder sheet and an AMB ceramic copper clad laminate. The composite solder sheet has low cost, high activity, and excellent brazing effect. When used in the preparation of AMB ceramic plates, it can effectively reduce the preparation cost and improve the preparation efficiency. The processed AMB ceramic copper clad laminate also has the characteristics of excellent interface bonding strength, lower weld void rate, higher joint reliability, etc.

[0005] In order to achieve the above purpose, the present invention adopts the following technical solutions: Firstly, the present invention provides a composite solder sheet, which is composed of an active metal foil and a copper-containing layer modified on its surface.

[0006] Preferably, the material of the active metal foil is selected from any one of titanium, zirconium, vanadium, and chromium, which are pure metals or alloys. These active metals can form good wettability and reactivity with the ceramic substrate and can form good bonding strength; compared with precious metals, they also have the advantage of low cost.

[0007] Preferably, the active metal foil is made of titanium metal or titanium alloy.

[0008] Preferably, the copper-containing layer is a copper metal layer and / or a copper alloy layer.

[0009] The present invention adopts a composite solder sheet containing an active metal layer, which has a structure of copper-containing layer / active metal layer / copper-containing layer. The active metal layer is a solder with excellent performance and low cost. The copper-containing layer is plated on the surface of the active metal layer, which not only protects the former and avoids the oxidation problem of the active metal during brazing, but also increases the compatibility and interface wettability of the solder and the copper substrate.

[0010] Preferably, the thickness of the active metal foil is 5-20μm; exemplary are 5μm, 6μm, 7μm, 8μm, 9μm, 9.5μm, 10μm, 11μm, 11.5μm, 12μm, 13μm, 13.5μm, 14μm, 15μm, 15.5μm, 16μm, 17μm, 17.5μm, 18μm, 20μm, etc.

[0011] Preferably, the ratio of the thickness of the copper-containing layer on the single-side surface of the active metal foil to the thickness of the active metal foil is 0.7-1.2:1; exemplary examples are 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, etc. The thickness ratio range can make the mass percentage of Cu:active metal (such as Ti, etc.) per unit area in the composite solder sheet close to that of the Cu-active metal eutectic alloy, so that the composite solder sheet has a lower melting point, and can wet the substrate faster and produce interfacial metallurgical reaction when used for brazing. In addition, the present invention is used in the form of sheets, which can not only realize the preparation of large-area and uniform solder sheets, but also be more convenient in application, can quickly meet the welding requirements of substrates of different areas, and improve welding efficiency, which overcomes the defects of the Cu-active metal eutectic alloy itself being brittle and unable to prepare large-area alloy sheets.

[0012] Preferably, the copper-containing layers on both sides of the active metal foil have the same or different thicknesses.

[0013] In one embodiment, the copper-containing layers on both sides of the active metal foil have the same thickness.

[0014] Preferably, the copper-containing layer is a copper metal layer.

[0015] Secondly, the present invention provides a method for preparing an AMB ceramic copper-clad laminate, wherein the ceramic copper-clad laminate comprises a copper substrate, a composite solder sheet, a ceramic sheet, a composite solder sheet, and a copper substrate arranged in sequence from top to bottom, and the preparation method comprises the following steps: S1. Depositing at least one copper-containing layer on both sides of the clean active metal foil to obtain a composite solder sheet; S2, placing the composite solder sheet between the ceramic sheet and the copper substrate, pressing the copper substrate with a pressing block and placing it in a vacuum brazing furnace; S3. Turn on the vacuum brazing furnace and start heating. When the furnace temperature rises to 350-885℃, keep it warm for 5-240min, then continue to heat it to 890-1100℃ and keep it warm for 3-120min, then cool it down.

[0016] By controlling the heating temperature of high-temperature brazing, the high-temperature elements are first diffused at the diffusion temperature to achieve alloying of the composite solder layer, and then the uniform melting of the solder and the wetting metallurgical reaction between the solder and the copper and ceramic substrate are achieved at the brazing temperature. In this process, the composite solder sheet is subjected to thermal diffusion alloying, which can further effectively avoid the oxidation problem of active metals during storage and brazing, thereby realizing the preparation of low-cost and high-reliability AMB ceramic copper-clad laminates.

[0017] Preferably, the active metal foil is made of any one of pure metals or alloys of titanium, zirconium, vanadium and chromium.

[0018] Preferably, the active metal foil is made of titanium metal or titanium alloy.

[0019] Preferably, the thickness of the active metal foil is 5-20 μm.

[0020] Preferably, the active metal foil is surface treated before step S1, and the surface treatment method includes but is not limited to at least one of pickling, alcohol washing, water washing, grinding, sandblasting, polishing, and hydrogenation to remove the oxide film on the surface of the active metal and reduce the thickness of the active metal foil.

[0021] Preferably, before step S1 is performed, the active metal foil is subjected to surface treatments of acid washing, ultrasonic alcohol washing and hydrogenation in sequence.

[0022] Preferably, the pickling adopts HF solution with a volume fraction of 5%-10%, more preferably 10%.

[0023] Preferably, anhydrous ethanol is used for ultrasonic alcohol washing.

[0024] Preferably, hydrogenation uses a mixture of concentrated hydrochloric acid and concentrated sulfuric acid, and the volume ratio of concentrated hydrochloric acid to concentrated sulfuric acid is 1.5-3, more preferably 3; the hydrogenation time is 20-60min. Hydrogenation treatment is the most critical process before surface deposition process, and its purpose is to remove the newly formed thin oxide film on the surface of the active metal foil, and to form a conductive protective film on its surface, and to allow slight corrosion to obtain good bonding between the active metal and the coating. The hydrogenation process must strictly control the selection of acid type, dosage and hydrogenation time to avoid incomplete surface treatment and excessive surface treatment that lead to poor coating effect, thereby causing the active metal to be unable to obtain good protection during brazing and uneven solder composition.

[0025] Preferably, the copper-containing layer in step S1 is a copper metal layer and / or a copper alloy layer.

[0026] Preferably, the deposition method of step S1 includes but is not limited to at least one of electroplating, chemical plating, thermal spraying, and magnetic sputtering, and electroplating is more preferred.

[0027] Preferably, the copper plating solution components for electroplating and depositing the copper-containing layer include: 50-90g / L copper pyrophosphate, 250-400g / L potassium phosphate trihydrate, 20-80g / L ammonium citrate and water; copper pyrophosphate provides a source of copper ions, and the higher the concentration, the faster the deposition rate, but at the same time, the grains of the coating, i.e., the copper-containing layer, will also become coarser; potassium phosphate trihydrate can improve the crystal state of the coating, improve the dispersibility and covering ability of the plating solution, and improve the quality of the coating, but when the concentration of potassium phosphate trihydrate is too low, it leads to poor anode solubility and increased crystal roughness of the coating, and when the concentration of potassium phosphate trihydrate is too high, it will reduce the cathode current efficiency; ammonium citrate can adjust the pH value of the copper plating solution within a suitable range, thereby improving the stability of the electroplating solution and the uniformity of the surface of the electroplated part. Control the components and concentration of the copper plating solution to ensure that the deposited copper-containing layer has good uniformity, thereby improving the strength of the weld.

[0028] Preferably, the current density of electroplating is 0.0002-0.0008A / mm 2 .

[0029] Preferably, the ratio of the thickness of the copper-containing layer on the single-side surface of the active metal foil to the thickness of the active metal foil is 0.7-1.2:1.

[0030] When the copper layer is too thick, the flatness of the active metal foil is reduced, the soldering rate of the brazing joint is reduced, and the excess copper hinders the reaction between the active elements and the ceramic, reducing the reliability of the welding joint; when it is too thin, the reaction layer aggregates, affecting the strength of the brazing joint. Only the appropriate thickness can match the mass percentage of the specific Cu-active metal eutectic alloy to obtain a lower melting point, better wetting and more efficient metallurgical reaction.

[0031] Preferably, the ceramic sheet is selected from any one of silicon nitride ceramics, alumina ceramics, aluminum nitride ceramics, ZTA ceramics, and beryllium oxide ceramics.

[0032] Preferably, the ceramic sheet and the copper substrate are surface treated before use, and the surface treatment methods include but are not limited to at least one of pickling, alcohol washing, water washing, grinding, sandblasting, polishing, and hydrogenation to remove surface oxides and oil stains.

[0033] Preferably, the pressure provided by the pressing block is 0.001-5MPa. Appropriate brazing pressure can enhance the fluidity of the solder, squeeze out the gas in the brazing interface, and thus reduce the void rate of the welding interface; secondly, it can promote close contact between the ceramic substrate or copper substrate and the solder, ensure that the solder fully wets the surface of the ceramic substrate or copper substrate, and enhance the bonding strength of the interface; thirdly, it can reduce the residual stress of the above substrates or welds; although appropriate pressure is beneficial to welding performance, excessive pressure may cause the ceramic substrate to crack and the solder to overflow. Therefore, the applied pressure needs to be carefully selected during the brazing process to achieve the best welding effect without compromising the integrity of the material. Preferably, in step S3, the temperature is first raised to 700-875°C, kept warm for 10-120min, and then raised to 890-1000°C, and kept warm for 10-60min. In the present invention, the diffusion temperature is most preferably controlled to be 700-875°C. At this temperature, the active metal elements and copper elements in the solder will diffuse to the connection interface between the solder and the ceramic substrate / copper substrate, and the Si element, N element, aluminum element, copper element, etc. present in the ceramic substrate or the copper substrate will also diffuse to the connection interface in small amounts, forming a reaction layer containing active metal nitrides, active metal silicides, active metal-Cu, etc. at the connection interface. The diffusion temperature can provide appropriate reaction energy to ensure good element diffusion effect and alloying degree of the interface layer or reaction layer; further, the temperature is most preferably controlled at a brazing temperature of 890-1000°C and kept warm, so that the solder is melted as a whole, and the best wetting metallurgical reaction is generated between the ceramic sheet and the copper substrate, and finally the weld strength is improved. When the above diffusion temperature and brazing temperature are too high, the decomposition and strength reduction of the parent material at the interface may be caused. In addition, the insulation time also needs to be strictly controlled. The appropriate insulation time can obtain the appropriate interface layer thickness and improve the weld strength, but when the insulation time is too long, the thickness of the interface layer increases, resulting in a decrease in weld strength.

[0034] Secondly, the present invention also provides an AMB ceramic copper-clad laminate prepared by the method, wherein the weld thickness of the AMB ceramic copper-clad laminate is 2-30 μm, the weld peel strength is ≥10 N / mm, and the weld porosity is <1%.

[0035] Preferably, the AMB ceramic copper clad laminate is used as a circuit substrate.

[0036] Beneficial effects of the present invention: The present invention adopts a copper-containing layer / active metal foil / copper-containing layer as a composite brazing material, avoiding the use of precious metals, and the composite solder is a sheet structure, which can realize the preparation of a large-area solder sheet with uniform composition, and is used in the preparation method of AMB ceramic copper-clad laminates, which can effectively reduce the cost of solder and process; (2) The present invention deposits a copper-containing layer on the surface of the active metal foil, which can effectively avoid the oxidation problem of the active metal during storage and brazing, reduce the oxygen content of the solder, ensure the uniformity of the overall composition of the solder, and improve the reliability of the joint; (3) The present invention optimizes the brazing process. First, the composite solder is kept warm below the brazing temperature to achieve interlayer diffusion and alloying. Then, the composite solder is kept warm at the brazing temperature to achieve overall melting of the solder and the wetting metallurgical reaction between the solder and the copper substrate and the ceramic sheet. This ensures the uniformity of the solder composition and the continuity of the metallurgical reaction with the brazing interface, reduces the void rate of the weld, and improves the interface bonding strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic diagram of the structure of the AMB ceramic copper clad laminate of the present invention;

[0038] Figure 2 This is a micrograph of the cross section of the weld of the ceramic copper clad laminate prepared in Example 1 of the present invention;

[0039] Figure 3 This is a micrograph of the cross section of the weld of the ceramic copper clad laminate prepared in Example 2 of the present invention;

[0040] Among them, ceramic sheet-1, composite solder sheet-2, copper substrate-3. DETAILED DESCRIPTION

[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example An embodiment of the present invention provides a composite solder sheet, which is composed of an active metal foil and a surface-modified copper-containing layer thereof; the material of the active metal foil is selected from any one of pure metals or alloys of titanium, zirconium, vanadium, and chromium, preferably titanium metal; the copper-containing layer is a copper metal layer and / or a copper alloy layer; the thickness of the active metal foil is 5-20 μm; the ratio of the thickness of the copper-containing layer on the single-side surface of the active metal foil to the thickness of the active metal foil is 0.7-1.2:1.

[0043] The embodiment of the present invention also provides a method for preparing an AMB ceramic copper-clad laminate, wherein the ceramic copper-clad laminate comprises a copper substrate 3, a composite solder sheet 2, a ceramic sheet 1, a composite solder sheet 2, and a copper substrate 3 arranged in sequence from top to bottom, and the structure is shown in the attached Figure 1 , the preparation method comprises the following steps: S1, depositing at least one copper-containing layer on both sides of the clean active metal foil to obtain a composite solder sheet 2; S2, placing the composite solder sheet 2 between the ceramic sheet 1 and the copper substrate 3, pressing the copper substrate 3 with a pressing block and placing it in a vacuum brazing furnace; S3. Turn on the vacuum brazing furnace and start heating. When the furnace temperature rises to 350-885℃, keep it warm for 5-240min, then continue to heat it to 890-1100℃ and keep it warm for 3-120min, then cool it down.

[0044] Before step S1 is performed, the active metal foil is subjected to surface treatments of pickling, ultrasonic alcohol washing and hydrogenation in sequence, wherein the pickling adopts HF solution with a volume fraction of 5-10%, the ultrasonic alcohol washing adopts anhydrous ethanol, the hydrogenation adopts a mixed solution of concentrated hydrochloric acid and concentrated sulfuric acid, the volume ratio of concentrated hydrochloric acid to concentrated sulfuric acid is 1.5-3, and the hydrogenation time is 20-60 minutes.

[0045] The deposition method of the copper-containing layer includes at least one of electroplating, chemical plating, thermal spraying, and magnetic sputtering, preferably electroplating; the copper plating solution components for depositing the copper-containing layer include: 50-90 g / L copper pyrophosphate, 250-400 g / L potassium phosphate trihydrate, 20-80 g / L ammonium citrate and water; the current density of the electroplating is 0.0002-0.0008 A / mm 2 .

[0046] The ceramic sheet 1 is selected from any one of silicon nitride ceramics, alumina ceramics, aluminum nitride ceramics, ZTA ceramics, and beryllium oxide ceramics.

[0047] The ceramic sheet 1 and the copper substrate 3 are surface treated before use, and the surface treatment method includes at least one of pickling, alcohol washing, water washing, grinding, sandblasting, polishing, and hydrogenation, preferably including pickling and ultrasonic alcohol washing.

[0048] The pressure provided by the pressing block is 0.001-5MPa.

[0049] Preferably, in S3, the temperature is first raised to 700-875°C, kept warm for 10-120 min, and then raised to 890-1000°C, kept warm for 10-60 min.

[0050] Example 1 This embodiment provides a composite solder sheet, which is composed of an active metal titanium foil and a surface-modified copper metal layer thereof; the thickness of the active metal titanium foil is 10 μm; the ratio of the thickness of the copper metal layer on a single side surface of the active metal titanium foil to the thickness of the active metal titanium foil is 1:1.

[0051] This embodiment also provides a method for preparing an AMB ceramic copper-clad laminate, wherein the ceramic copper-clad laminate comprises a copper substrate 3, a composite solder sheet 2, a silicon nitride ceramic sheet 1, a composite solder sheet 2, and a copper substrate 3 arranged in sequence from top to bottom, and the structure is shown in the attached Figure 1 , the preparation method comprises the following steps: S1, taking a 10 μm thick active metal titanium foil, and sequentially performing acid washing, ultrasonic alcohol washing and hydrogenation treatment on it; The pickling used a 10% HF solution with a pickling time of 5 seconds, the alcohol washing used anhydrous ethanol (ultrasonic power and time were 80 W and 5 minutes, respectively), and the hydrogenation treatment was to immerse the titanium foil in a mixture of concentrated hydrochloric acid and concentrated sulfuric acid with a volume ratio of 3:1 and leave it for 45 minutes. After the immersion, it was taken out and washed with deionized water.

[0052] S2. Electroplating a copper metal layer on both sides of the titanium foil to obtain a composite solder sheet 2; the composition of the copper plating solution used is 75 g / L copper pyrophosphate, 310 g / L potassium phosphate trihydrate, 40 g / L ammonium citrate and water, and the current density used for electroplating is 0.0007 A / mm 2 , the thickness of the copper metal layer deposited on one side of the titanium foil after electroplating is 10μm.

[0053] S3, the surfaces of the silicon nitride ceramic sheet 1 (thickness 0.32 mm) and the copper substrate 3 (thickness 0.8 mm) are sequentially pickled and ultrasonically cleaned with alcohol, and the pickling and ultrasonic cleaning operations are the same as (1); according to the attached Figure 1 The composite solder sheet is placed between the silicon nitride ceramic sheet 1 and the copper substrate 3, and the copper substrate 3 is pressed by a pressing block. The pressure generated by the pressing block is 7.0×10 -3 MPa; put the pressed structure into the vacuum brazing furnace.

[0054] S4, open the vacuum system of the vacuum brazing furnace, and wait until the vacuum degree of the furnace chamber reaches 6.0×10 -3 The heating system was turned on at 850°C and kept at that temperature for 30 minutes. The temperature was then raised to 920°C and kept at that temperature for 10 minutes. After the insulation, the sample was cooled to room temperature with the furnace to complete the preparation of the ceramic copper clad laminate. The weld thickness was about 12μm.

[0055] Attached Figure 2 This is a micrograph of the cross-section of the weld of the ceramic copper-clad laminate prepared in Example 1. As can be seen from the figure, the solder wetting performance at the interface is excellent and the solder distribution is also very uniform.

[0056] Example 2 This embodiment provides a composite solder sheet, which is composed of an active metal titanium foil and a copper metal layer modified on its surface; the thickness of the active metal titanium foil is 20 μm; the ratio of the thickness of the copper metal layer on the single-side surface of the active metal titanium foil to the thickness of the active metal titanium foil is 0.9:1.

[0057] This embodiment also provides a method for preparing an AMB ceramic copper-clad laminate, wherein the ceramic copper-clad laminate comprises a copper substrate 3, a composite solder sheet 2, a silicon nitride ceramic sheet 1, a composite solder sheet 2, and a copper substrate 3 arranged in sequence from top to bottom, and the structure is shown in the attached Figure 1 , the preparation method comprises the following steps: S1, taking a 20 μm thick active metal titanium foil, and sequentially performing acid washing, ultrasonic alcohol washing and hydrogenation treatment on it; The pickling used a 10% HF solution with a pickling time of 7 seconds, the alcohol washing used anhydrous ethanol (ultrasonic power and time were 80 W and 5 min, respectively), and the hydrogenation treatment was to immerse the titanium foil in a mixture of concentrated hydrochloric acid and concentrated sulfuric acid with a volume ratio of 3:1 and leave it for 45 minutes. After the immersion, it was taken out and washed with deionized water.

[0058] S2. Electroplating a copper metal layer on both sides of the titanium foil to obtain a composite solder sheet; the composition of the copper plating solution used is 75g / L copper pyrophosphate, 310g / L potassium phosphate trihydrate, 40g / L ammonium citrate and water, and the current density used for electroplating is 0.0007A / mm 2 , the thickness of the copper metal layer deposited on one side of the titanium foil after electroplating is 18μm.

[0059] S3, the surfaces of the silicon nitride ceramic sheet 1 (thickness 0.32 mm) and the copper substrate 3 (thickness 0.8 mm) are sequentially pickled and ultrasonically cleaned with alcohol, and the pickling and ultrasonic cleaning operations are the same as (1); according to the attached Figure 1 The composite solder sheet 2 is placed between the silicon nitride ceramic sheet 1 and the copper substrate 3, and the copper substrate 3 is pressed by a pressing block. The pressure generated by the pressing block is 7.0×10 -3 MPa; put the pressed structure into the vacuum brazing furnace.

[0060] S4, open the vacuum system of the vacuum brazing furnace, and wait until the vacuum degree of the furnace chamber reaches 6.0×10 -3 Pa, and the heating system was turned on, and the furnace temperature was kept at 860℃ for 60 minutes, and then the temperature was continued to rise to 920℃ and kept for 60 minutes; after the insulation, the sample was cooled to room temperature with the furnace, and the preparation of the ceramic copper clad laminate was completed, in which the weld thickness was about 20μm.

[0061] Attached Figure 3This is a micrograph of the cross-section of the weld of the ceramic copper-clad laminate prepared in Example 2. It can be seen from the figure that the solder has sufficient diffusion and wetting properties between the ceramic substrate and the copper substrate at the welding interface, and the solder distribution at the interface is relatively uniform.

[0062] Example 3 This embodiment provides a composite solder sheet, which is composed of an active metal titanium foil and a copper metal layer modified on its surface; the thickness of the active metal titanium foil is 15 μm; the ratio of the thickness of the copper metal layer on the single-side surface of the active metal titanium foil to the thickness of the active metal titanium foil is 0.7:1.

[0063] This embodiment also provides a method for preparing an AMB ceramic copper-clad laminate, wherein the ceramic copper-clad laminate comprises a copper substrate 3, a composite solder sheet 2, a silicon nitride ceramic sheet 1, a composite solder sheet 2, and a copper substrate 3 arranged in sequence from top to bottom, and the structure is shown in the attached Figure 1 , the preparation method comprises the following steps: S1, taking a 15 μm thick active metal titanium foil, and sequentially performing acid washing, ultrasonic alcohol washing and hydrogenation treatment on it; The pickling used an 8% HF solution with a pickling time of 10 seconds, the alcohol washing used anhydrous ethanol (ultrasonic power and time were 80 W and 5 minutes, respectively), and the hydrogenation treatment was to immerse the titanium foil in a mixture of concentrated hydrochloric acid and concentrated sulfuric acid with a volume ratio of 2:1 and leave it for 60 minutes. After the immersion, it was taken out and washed with deionized water.

[0064] S2. Electroplating a copper metal layer on both sides of the titanium foil to obtain a composite solder sheet; the composition of the copper plating solution used is 50 / L copper pyrophosphate, 250g / L potassium phosphate trihydrate, 80g / L ammonium citrate and water, and the current density used for electroplating is 0.0008A / mm 2 , the thickness of the copper metal layer deposited on one side of the titanium foil after electroplating is 10.5μm.

[0065] S3, the surfaces of the silicon nitride ceramic substrate 1 (thickness 0.8 mm) and the copper substrate 3 (thickness 1.0 mm) are sequentially pickled and ultrasonically cleaned with alcohol, and the pickling and ultrasonic cleaning operations are the same as (1); according to the attached Figure 1 The composite solder sheet 2 is placed between the silicon nitride ceramic sheet 1 and the copper substrate 3, and the copper substrate 3 is pressed by a pressing block, the pressure generated by the pressing block is 5 MPa; the pressed structure is placed in a vacuum brazing furnace.

[0066] S4, open the vacuum system of the vacuum brazing furnace, and wait until the vacuum degree of the furnace chamber reaches 9.0×10 -3 The heating system was turned on at 9:00 p.a., and the furnace temperature was kept at 875°C for 10 minutes, then the temperature was continued to rise to 1000°C and kept at this temperature for 10 minutes; after the insulation, the sample was cooled to room temperature with the furnace, and the preparation of the ceramic copper clad laminate was completed.

[0067] Example 4 This embodiment provides a composite solder sheet, which is composed of an active metal titanium foil and a copper metal layer modified on its surface; the thickness of the active metal titanium foil is 5 μm; the ratio of the thickness of the copper metal layer on the single-side surface of the active metal titanium foil to the thickness of the active metal titanium foil is 1.2:1.

[0068] This embodiment also provides a method for preparing an AMB ceramic copper-clad laminate, wherein the ceramic copper-clad laminate comprises a copper substrate 3, a composite solder sheet 2, a silicon nitride ceramic sheet 1, a composite solder sheet 2, and a copper substrate 3 arranged in sequence from top to bottom, and the structure is shown in the attached Figure 1 , the preparation method comprises the following steps: S1, taking a 5 μm thick active metal titanium foil, and sequentially performing acid washing, ultrasonic alcohol washing and hydrogenation treatment on it; The pickling used a 5% HF solution with a pickling time of 20 seconds, the alcohol washing used anhydrous ethanol (ultrasonic power and time were 80 W and 5 minutes, respectively), and the hydrogenation treatment was to immerse the titanium foil in a mixture of concentrated hydrochloric acid and concentrated sulfuric acid with a volume ratio of 3:1 and leave it for 60 minutes. After the immersion, it was taken out and washed with deionized water.

[0069] S2. Electroplating a copper metal layer on both sides of the titanium foil to obtain a composite solder sheet; the composition of the copper plating solution used is 90 / L copper pyrophosphate, 400g / L potassium phosphate trihydrate, 20g / L ammonium citrate and water, and the current density used for electroplating is 0.0002A / mm 2 , the thickness of the copper metal layer deposited on one side of the titanium foil after electroplating is 6μm.

[0070] S3, the surfaces of the silicon nitride ceramic sheet 1 (thickness 0.32 mm) and the copper substrate 3 (thickness 0.5 mm) are sequentially pickled and ultrasonically cleaned with alcohol, and the pickling and ultrasonic cleaning operations are the same as (1); according to the attached Figure 1 The composite solder sheet 2 is placed between the silicon nitride ceramic sheet 1 and the copper substrate 3, and the copper substrate 3 is pressed by a pressing block, the pressure generated by the pressing block is 0.001MPa; the pressed structure is placed in a vacuum brazing furnace.

[0071] S4, open the vacuum system of the vacuum brazing furnace, and wait until the vacuum degree of the furnace chamber reaches 9.0×10 -3 The heating system was turned on at 900°C and the furnace temperature was kept at 700°C for 120 minutes. The temperature was then raised to 890°C and kept at this temperature for 60 minutes. After the insulation, the sample was cooled to room temperature with the furnace to complete the preparation of the ceramic copper clad laminate.

[0072] Comparative Example 1 This comparative example provides a solder sheet, which is an active metal titanium foil with a thickness of 10 μm.

[0073] This comparative example also provides a method for preparing an AMB ceramic copper-clad laminate, wherein the ceramic copper-clad laminate comprises a copper substrate, a solder sheet, a silicon nitride ceramic sheet, a solder sheet, and a copper substrate arranged in sequence from top to bottom, and the preparation method comprises the following steps: S1, taking a 10 μm thick active metal titanium foil as a solder sheet, and sequentially performing acid washing, ultrasonic alcohol washing and hydrogenation treatment on it; The pickling used a 10% HF solution with a pickling time of 5 seconds, the alcohol washing used anhydrous ethanol (ultrasonic power and time were 80 W and 5 minutes, respectively), and the hydrogenation treatment was to immerse the titanium foil in a mixture of concentrated hydrochloric acid and concentrated sulfuric acid with a volume ratio of 3:1 and leave it for 45 minutes. After the immersion, it was taken out and cleaned.

[0074] S2. The surfaces of the silicon nitride ceramic sheet (thickness 0.32 mm) and the copper substrate (thickness 0.8 mm) were pickled and ultrasonically cleaned in turn. The pickling and ultrasonic cleaning operations were the same as (1). The solder sheet was placed between the silicon nitride ceramic sheet and the copper substrate, and the copper substrate was pressed with a pressing block. The pressure generated by the pressing block was 7×10 -3 MPa; put the pressed structure into the vacuum brazing furnace.

[0075] S3, open the vacuum system of the vacuum brazing furnace, and wait until the vacuum degree of the furnace chamber reaches 6.0×10 -3 The heating system was turned on at 850°C and kept at that temperature for 30 minutes. The temperature was then raised to 920°C and kept at that temperature for 10 minutes. After the heat preservation, the sample was cooled to room temperature with the furnace to complete the preparation of the ceramic copper clad laminate.

[0076] Comparative Example 2 This comparative example provides a method for preparing a composite solder sheet and an AMB ceramic copper-clad laminate, which is basically the same as Example 1, except that: the ratio of the thickness of the copper metal layer on the single-side surface of the active metal foil to the thickness of the active metal titanium foil is 1.6:1; the thickness of the copper metal layer deposited on the single side of the titanium foil after electroplating is 16 μm.

[0077] Comparative Example 3 This comparative example provides a method for preparing a composite solder sheet and an AMB ceramic copper-clad laminate, which is basically the same as Example 1, except that: the thickness of the active metal titanium foil is 30 μm; the ratio of the thickness of the copper metal layer on the single-side surface of the active metal foil to the thickness of the active metal titanium foil is 1:1, and the thickness of the copper metal layer deposited on the single side of the titanium foil after electroplating is 30 μm.

[0078] Comparative Example 4 This comparative example provides a method for preparing an AMB ceramic copper-clad laminate, which is basically the same as Example 1, except that the copper plating solution components for depositing the copper-containing layer include: 105 g / L copper pyrophosphate, 420 g / L potassium phosphate trihydrate, 60 g / L ammonium citrate and water.

[0079] Comparative Example 5 This comparative example provides a method for preparing an AMB ceramic copper-clad laminate, which is basically the same as that of Example 1, except that the pressure provided by the pressing block is 6 MPa.

[0080] Comparative Example 6 This comparative example provides a preparation method of an AMB ceramic copper-clad laminate, which is basically the same as Example 1, except that: the hydrogenation treatment in S1 is to immerse the titanium foil in a mixture of concentrated hydrochloric acid and concentrated sulfuric acid in a volume ratio of 1:1 and leave it for 60 minutes, and then take it out and wash it after the immersion is completed.

[0081] Comparative Example 7 This comparative example provides a method for preparing an AMB ceramic copper-clad laminate, which is basically the same as that of Example 1, except that: S4 is to open the vacuum system of the vacuum brazing furnace, and wait until the vacuum degree of the furnace chamber is 6.0×10 -3 Pa, the heating system is turned on, the temperature is raised to 920℃ and kept warm for 30 minutes; after the insulation, the sample is cooled to room temperature with the furnace, and the preparation of the ceramic copper clad laminate is completed.

[0082] Comparative Example 8 This comparative example provides a method for preparing an AMB ceramic copper-clad laminate, which is basically the same as that of Example 1, except that: S4 is to open the vacuum system of the vacuum brazing furnace, and wait until the vacuum degree of the furnace chamber is 6.0×10 -3 The heating system was turned on at 900°C and the furnace temperature was kept at 600°C for 40 minutes. The temperature was then raised to 1000°C and kept at this temperature for 10 minutes. After the insulation, the sample was cooled to room temperature with the furnace to complete the preparation of the ceramic copper clad laminate.

[0083] Performance testing method: 1. Peel strength: Tested in accordance with GB / T 4722-2017 standard; 2. Porosity: An ultrasonic acoustic microscope was used to characterize the welding rate of the joint. The scanning range was the area of ​​the complete welding joint corresponding to the composite solder sheet. The porosity was calculated using the Image-J software using the obtained data.

[0084] The performance test results are shown in Table 1.

[0085] Table 1 Test results of peel strength and joint porosity of AMB ceramic copper clad laminates prepared by different methods

[0086]

[0087] Analysis: From the test results of the embodiment, it can be seen that the composite solder sheet and the corresponding preparation method of this patent can obtain a ceramic copper clad laminate with excellent performance.

[0088] In Comparative Example 1, active metal foil is directly used as solder sheet, and the peel strength of the processed AMB ceramic copper-clad laminate is reduced and the porosity is increased. This may be because when the surface of the active metal foil is not protected by the copper-containing layer, the solder sheet may be oxidized during the brazing process, resulting in a high oxygen content in the weld area, and the interface wetting effect between the active metal foil and the copper substrate and the ceramic substrate is poor, resulting in uneven composition in the weld area. In Comparative Example 2, when the thickness of the copper metal layer deposited on the surface of the metal foil is too large, the flatness of the active metal foil is reduced, the brazing joint welding rate is reduced, and the excess copper will also hinder the reaction of the active element with the ceramic, resulting in a significant reduction in the reliability of the welded joint.

[0089] In Comparative Example 3, a thicker active metal titanium foil is used, which may lead to an increase in the thickness of the weld area and increase the residual stress generated by the mismatch of thermal expansion coefficients during welding, ultimately resulting in a decrease in weld strength. In addition, excessively thick active metal not only increases material costs, but also requires higher welding temperatures and pressures.

[0090] In Comparative Example 4, the composition of the copper electroplating solution was adjusted. When the copper ion concentration was too high, the electroplating deposition rate was also fast, and the roughness of the deposited copper metal layer would become larger, which would also affect the reliability of the weld by affecting the composition uniformity of the welding area.

[0091] In Comparative Example 5, a larger pressing pressure will cause the solder to overflow and thus affect the welding effect of the weld area.

[0092] Comparative Example 6 proves that the hydrogenation process will also significantly affect the welding reliability. Improper acid composition ratio will cause incomplete surface treatment or excessive surface treatment, which will affect the deposition effect of the electroplating layer, resulting in the active metal not being well protected during the brazing process and uneven solder composition.

[0093] The results of Comparative Examples 7 and 8 both confirm that only by strictly controlling the welding temperature and ensuring that the welding area has a suitable diffusion and alloying process and wetting metallurgical reaction at a specific temperature can the performance of the welded joint be improved.

[0094] Therefore, in the process of preparing ceramic copper clad laminates using this patent, the corresponding preparation step regulations should be followed.

[0095] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0096] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite solder sheet, characterized in that: The composite solder sheet is composed of an active metal foil and a surface-modified copper-containing layer thereof; the material of the active metal foil is selected from any one of pure metals or alloys of titanium, zirconium, vanadium and chromium; the copper-containing layer is a copper metal layer and / or a copper alloy layer; the ratio of the thickness of the copper-containing layer on the single-side surface of the active metal foil to the thickness of the active metal foil is 0.7-1.2:

1.

2. The composite solder sheet according to claim 1, characterized in that: The active metal foil is made of titanium metal or titanium alloy.

3. The composite solder sheet according to claim 1 or 2, characterized in that: The thickness of the active metal foil is 5-20 μm.

4. A method for preparing an AMB ceramic copper-clad laminate, the ceramic copper-clad laminate comprising a copper substrate (3), a composite solder sheet (2), a ceramic sheet (1), a composite solder sheet (2), and a copper substrate (3) arranged in sequence from top to bottom, characterized in that: The preparation method comprises the following steps: S1, depositing at least one copper-containing layer on both sides of the clean active metal foil to obtain a composite solder sheet (2); S2, placing the composite solder sheet (2) between the ceramic sheet (1) and the copper substrate (3), pressing the copper substrate (3) with a pressing block and placing the pressing block in a vacuum brazing furnace; S3, open the vacuum brazing furnace and start heating, when the furnace temperature rises to 350-885°C, keep it warm for 5-240 minutes, then continue to heat it to 890-1100°C and keep it warm for 3-120 minutes, and then cool it down; the composite solder sheet (2) is the composite solder sheet according to any one of claims 1 to 3.

5. The preparation method according to claim 4, characterized in that: Before step S1 is performed, the active metal foil is subjected to surface treatment, and the surface treatment method includes at least one of pickling, alcohol washing, water washing, grinding, sandblasting, polishing, and hydrogenation.

6. The preparation method according to claim 5, characterized in that: The pickling uses HF solution with a volume fraction of 5%-10%; the ultrasonic alcohol washing uses anhydrous ethanol; the hydrogenation uses a mixture of concentrated hydrochloric acid and concentrated sulfuric acid, and the volume ratio of concentrated hydrochloric acid to concentrated sulfuric acid is 1.5-3.

7. The preparation method according to claim 4, characterized in that: The pressure provided by the pressing block is 0.001-5MPa.

8. The preparation method according to claim 4, characterized in that: In step S3, the temperature is first raised to 700-875° C., kept warm for 10-120 min, and then raised to 890-1000° C., kept warm for 10-60 min.

9. The preparation method according to claim 4, characterized in that: The ceramic sheet (1) and the copper substrate (3) are subjected to surface treatment before use, wherein the surface treatment method comprises at least one of pickling, alcohol washing, water washing, grinding, sandblasting, polishing, and hydrogenation.

10. The preparation method according to any one of claims 4 to 9, characterized in that: The weld thickness of the AMB ceramic copper-clad laminate is 2-30 μm, the weld peel strength is ≥10 N / mm, and the weld porosity is <1%.

Citation Information

Patent Citations

  • AMB ceramic-metal brazing method

    CN113953609A

Cited By

  • Nano-copper sintered ceramic substrate and preparation method thereof

    CN120097747A

  • Nano-copper sintered ceramic substrate and preparation method thereof

    CN120097747B

  • Active composite brazing filler metal suitable for welding ceramic and copper material and preparation method of active composite brazing filler metal

    CN120717802A

  • CTE gradient transition tin-based composite solder and application thereof in power module connection

    CN121946061A